Pengaruh Penambahan Katalis Aluminium Oksida Terhadap Emisi Gas Buang dan Konsumsi Bahan Bakar Pada Mesin Pembangkit Tipe Mini - bayhaqi, ahmad bayhaqi; Djoko Wahyudi; Muhammad Fathuddin Noor; Dani Hari Tunggal Prasetiyo (Jurnal Teknik Juara Aktif Global Optimis, 2024)
In line with development, human daily activities are very dependent on electrical technology so that its fulfillment needs to be paid close attention. Given this, the use of mini type power plants or generators is very necessary, especially when the main supply from PLN experiences disruption. Apart from that, currently almost all electrical energy supplies still depend on the use of fossil energy sources which, if used continuously, will cause their availability to decrease and the effects of environmental pollution from the combustion process. To prevent this from happening, efforts are needed to increase the efficiency of using machines that consume fossil fuels and reduce the effects of environmental pollution due to exhaust emissions. Therefore, the aim of this research is to determine the effect of adding an alumina catalyst on exhaust emissions and fuel consumption in engines using experimental methods with load variations of 0 Watt, 250 Watt, 500 Watt and 750 Watt. From the research results, after mixing the catalyst and fuel, it was found that the concentration of CO, CO2, O2 and H2S exhaust gas emissions decreased and fuel consumption could also be reduced from 100% to 66% at a load condition of 750 Watts.